Paternal-age-related de novo mutations and risk for five disorders - Jacob L. Taylor (Nature Portfolio, 2019)
Advanced paternal age associates with increased risk for psychiatric and developmental disorders in offspring. Here, Taylor et al. utilize parent-child trio exome sequencing data sets to estimate the contribution of paternal age-related de novo mutations to multiple disorders, including heart disease and schizophrenia.